2008
DOI: 10.1210/en.2007-1028
|View full text |Cite
|
Sign up to set email alerts
|

Preadipocyte 11β-Hydroxysteroid Dehydrogenase Type 1 Is a Keto-Reductase and Contributes to Diet-Induced Visceral Obesity in Vivo

Abstract: Glucocorticoid excess promotes visceral obesity and cardiovascular disease. Similar features are found in the highly prevalent metabolic syndrome in the absence of high levels of systemic cortisol. Although elevated activity of the glucocorticoid-amplifying enzyme 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1) within adipocytes might explain this paradox, the potential role of 11beta-HSD1 in preadipocytes is less clear; human omental adipose stromal vascular (ASV) cells exhibit 11beta-dehydrogenase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…A very recent study supports this view demonstrating that the mouse adipose stromal vascular cells (ASVCs) express H6PD, consistent with dominant reductase activity of HSD11B1 (De Sousa-Peixoto et al 2008). Conflicting results were previously reported by others in human ASVCs showing a dehydrogenase-to-reductase switch during the adipogenic differentiation (Bujalska et al 2005, Nashev et al 2007.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…A very recent study supports this view demonstrating that the mouse adipose stromal vascular cells (ASVCs) express H6PD, consistent with dominant reductase activity of HSD11B1 (De Sousa-Peixoto et al 2008). Conflicting results were previously reported by others in human ASVCs showing a dehydrogenase-to-reductase switch during the adipogenic differentiation (Bujalska et al 2005, Nashev et al 2007.…”
Section: Discussionsupporting
confidence: 65%
“…ASVCs are a heterogeneous population including preadipocytes, fibrocytes, monocytes, and endothelial cells. Interestingly, HSD11B1 is expressed in preadipocytes only, at levels comparable with differentiated adipocytes (De Sousa Peixoto et al 2008). The cellular heterogeneity of the preparation might thus explain the relatively high dehydrogenase activity before adipogenic differentiation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…63,64 There is evidence that 11β-HSD-1 activity is impaired in the liver but enhanced in adipose tissue in obese human patients. 33,65 Furthermore, the adverse metabolic complications of obesity in mice are prevented by 11β-HSD-1 gene deletion, 66 whereas overexpression of the enzyme in adipose tissue results in metabolic abnormalities. 67 Studies on obese and lean human individuals have demonstrated increased adipose tissue 11β-HSD-1 expression in obese subjects 68 and a direct association between 11β-HSD-1 levels and metabolic abnormalities in obese women.…”
Section: Glucocorticoids and Dyslipidemia/obesitymentioning
confidence: 99%
“…In our own experiments, we have shown expression and activity of 11β-HSD1 in mouse bone marrow-derived and thioglycollate-elicited peritoneal Mφ (>5 pmol corticosterone/h/10 6 cells) . Moreover, although bone marrow-derived Mφ readily reactivate glucocorticoids , immunofluorescence suggests Page 5 of 23 A c c e p t e d M a n u s c r i p t 5 that even so, 11β-HSD1 levels are relatively low in both bone marrow-derived ("resting") Mφ and in resident adipose tissue Mφ from normal lean mice (De Sousa Peixoto et al, 2008). Mφ expression of 11β-HSD1 may be highly dependent upon polarisation.…”
Section: β-Hsd1 and The Inflammatory Response 11β-hsd1 Is Expressedmentioning
confidence: 99%